The Influence of Micro-Emotions on Customer Loyalty: A Regression Analysis - Ago, Gordius (ProBisnis : Jurnal Manajemen, 2025)
The aim of this study is to investigate the impact of product design conformity, promotional communication tone, and symbol usage on customer loyalty toward Head & Shoulders shampoo. Understanding these factors essential for companies operating highly competitive consumer markets, where building and sustaining customer loyalty a key success driver. This research employs a quantitative research design with an associative-descriptive approach. Data were collected through a structured questionnaire distributed to 100 respondents, selected using simple random sampling ensure equal representation of the target population. This Analysis examine the connections between the independent variables, multiple linear regression was used product design conformity, promotional communication tone, and symbol usage and the dependent variable customer loyalty. Validity and reliability tests confirmed that the instruments were appropriate, with Cronbach's Alpha readings that are higher above the permissible limit of 0.70. Classical assumption tests showed the data met the required conditions for regression analysis. The main outcomes revealed that product design conformity did not significantly impact the loyalty of customers. In contrast, promotional communication tone and symbol usage demonstrated significant positive effects. The overall With an R2 value of 0.620, the regression model was statistically significant, suggesting that 62% of the variance in customer loyalty is elucidated by the independent factors. The study concludes that customer loyalty toward Head & Shoulders is strongly influenced by communication tone and symbol usage, while product design doesn’t play a significant role. This highlights the importance for marketers to prioritize effective promotional communication and consistent symbolic branding strategies in order to strengthen customer loyalty.